2022
DOI: 10.1186/s13002-022-00548-2
|View full text |Cite
|
Sign up to set email alerts
|

Short-term temporal analysis and children's knowledge of the composition of important medicinal plants: the structural core hypothesis

Abstract: Background Measures of the importance of medicinal plants have long been used in ethnobotany and ethnobiology to understand the influence of social-ecological system factors in the formation of individuals’ differential knowledge and use. However, there is still a gap in empirical studies that seek to understand the temporal aspects of this process. Methods To overcome this issue, we used the concept of the structural core of medicinal plants, a th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 69 publications
(78 reference statements)
1
2
0
Order By: Relevance
“…In addition, these observations have also been highlighted for food botanical resources, such as the diversity of ethnospecies of "yuca" (Manihot esculenta) in rural communities [35]. Thus, employing network analysis methods, the re ections based on extensive ethnobotanical surveys agree with the coreperiphery structure observed in this study [18,[28][29][30][31][32]. Now, if the core-periphery structure is supported, the question arises: What might be the possible reasons for consensus on the core species?…”
Section: Discussionsupporting
confidence: 81%
“…In addition, these observations have also been highlighted for food botanical resources, such as the diversity of ethnospecies of "yuca" (Manihot esculenta) in rural communities [35]. Thus, employing network analysis methods, the re ections based on extensive ethnobotanical surveys agree with the coreperiphery structure observed in this study [18,[28][29][30][31][32]. Now, if the core-periphery structure is supported, the question arises: What might be the possible reasons for consensus on the core species?…”
Section: Discussionsupporting
confidence: 81%
“…Other information regarding use, collection sites, and preparation methods was restricted to a very few participants. This demonstrates the gap in knowledge transmission, a common threat to traditional knowledge observed elsewhere (Geissler et al, 2002;Bruschi et al, 2019;Sousa et al, 2022).…”
Section: Demography and Knowledge Distribution Among Respondentsmentioning
confidence: 79%
“…Beyond the aforementioned lack of research on integrating medicinal herbs into environmental education in Central Europe (except Malatinszky, 2007;Azevedo et al, 2015), we identified interesting experiences in the Latin American dialogues on critical environmental pedagogy after Paulo Freire and Enrique Leff that address the intertwined environmental and educational crises (e.g., de Oliveira Martins and Ramos Araujo, 2021) and successfully integrate traditional knowledge of medicinal plants into rural school biology curricula in southern Brazil (Vinholi Júnior and Gonçalves de Azevedo, 2020). There is evidence that this practice reduces the distance both between school and regional culture and between school and everyday life, preserving cultural identity, traditional knowledge of medicinal plants, their meaning, symbolism, magic and reality (Vinholi Júnior and Vargas, 2014;Vinholi Júnior and Vargas, 2015;Souza Silva and Santos Baptista, 2018;Sousa et al, 2022;Ursi et al, 2018). In addition, the use of medicinal plants as an "educational tool" increases environmental literacy, including species knowledge, and uses the school's immediate environment as a triple didactic resource: First, to explore and discover the world through observation and contact; second, as a starting point for the development of integrated learning projects; and third, as a means to transform desires and feelings into active proposals, opportunities to change reality, and meaningful learning as a basis for emancipated citizenship (Säumel et al, 2017;Vinholi Júnior and Gonçalves de Azevedo, 2020).…”
Section: Discussionmentioning
confidence: 99%